Percutaneous kidney ablation: a good option in selected cases - Weprin, Samuel; Veccia, Alessandro; Autorino, Riccardo (Annals of Translational Medicine, 2019)
Partial nephrectomy (PN) has been recognized as the gold standard for definitive treatment of cT1 renal tumors. However, percutaneous ablation (PA) is widely regarded as an acceptable alternative in select patients. Current the American Urological Association (AUA) guidelines view both PN and PA as first-line options in T1a (